1972
DOI: 10.4315/0022-2747-35.7.436
|View full text |Cite
|
Sign up to set email alerts
|

The Propionic-Acid Bacteria-a Reviewiii. Miscellaneous Metabolic Activities1

Abstract: This is the third and final section of a review of the propionic-acid bacteria. This section discusses some of their miscellaneous metabolic activities such as: erythritol metabolism, formation of diacetyl-acetoin and vitamin B12, production of volatile compounds not previously mentioned, propionin (an antiviral agent), lipids and phospholipids, and slime formation, Concluding comments provide a brief summary of particular points of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…On the other hand, if propionic acid fermentation was carried out by using molasses in a two-step-process, a high propionic acid production should be accompanied with a high yield of biomass, which would be useful for an eventual extraction of vitamin B 12 [17,18]. Temperature [16] and pH control [18] are two factors that determine high yields.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, if propionic acid fermentation was carried out by using molasses in a two-step-process, a high propionic acid production should be accompanied with a high yield of biomass, which would be useful for an eventual extraction of vitamin B 12 [17,18]. Temperature [16] and pH control [18] are two factors that determine high yields.…”
Section: Discussionmentioning
confidence: 98%
“…They could be used for the industrial production of vitamin B12, and they could serve as alternate sources of natural food preservatives such as propionic and acetic acid. Moreover, propionic acid bacteria play an important role in the production of Swiss-type cheeses [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Diacetyl and acetoin can be produced by Prop. shermanii from citrate, glucose or lactate (Hettinga and Reinbold, 1972). Also, Drinan et al (1976) reported that some strains of L. plantantm produced acetoin from glucose.…”
Section: Chemical Analysismentioning
confidence: 98%